2020
DOI: 10.2196/16981
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Exacerbation Prediction and Risk Factor Analysis Based on a Time-Sensitive, Attentive Neural Network: Retrospective Cohort Study

Abstract: Background Asthma exacerbation is an acute or subacute episode of progressive worsening of asthma symptoms and can have a significant impact on patients’ quality of life. However, efficient methods that can help identify personalized risk factors and make early predictions are lacking. Objective This study aims to use advanced deep learning models to better predict the risk of asthma exacerbations and to explore potential risk factors involved in progre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 52 publications
0
40
0
1
Order By: Relevance
“…For example, an artificial neural network was used to analyze clinical data and create an automated pediatric asthma severity score, which showed better performance than the pediatric asthma score and could therefore help manage pediatric asthma exacerbation in the pediatric intensive care unit 54 . Similarly, a retrospective cohort study of 31,433 adult asthma patients reported a time-sensitive predictive model based on an artificial neural network, which integrated clinical variables in the observed time window to predict asthma exacerbation 55 . In addition, a modified artificial neural network was applied to predict emergency department visits of asthma and COPD patients due to exacerbation.…”
Section: Ai/ml and Asthmamentioning
confidence: 99%
“…For example, an artificial neural network was used to analyze clinical data and create an automated pediatric asthma severity score, which showed better performance than the pediatric asthma score and could therefore help manage pediatric asthma exacerbation in the pediatric intensive care unit 54 . Similarly, a retrospective cohort study of 31,433 adult asthma patients reported a time-sensitive predictive model based on an artificial neural network, which integrated clinical variables in the observed time window to predict asthma exacerbation 55 . In addition, a modified artificial neural network was applied to predict emergency department visits of asthma and COPD patients due to exacerbation.…”
Section: Ai/ml and Asthmamentioning
confidence: 99%
“…The data modality of structured EHR We define structured EHR data of each patient as a sequence of visits, each as a list of codes. This is a classic formulation commonly used in the literature 12,[49][50][51] . The codes within a visit can be either ordered or unordered.…”
Section: Introductionmentioning
confidence: 99%
“…IH, UWM, KPSC, and many other health care systems use IDM and use inaccurate predictive models with AUC<0.8 and sensitivity ≤49% for preventive care via care management [22,[24][25][26][46][47][48][49][50][51][52][53][54][55][56][57]. Similar to our recent work of using IH, UWM, and KPSC data to greatly increase prediction accuracy for hospital use for asthma [43][44][45] related to exacerbation proneness, we expect our models predicting exacerbation proneness to be more accurate than those inaccurate models, benefit many patients, and have practical value.…”
Section: Using Our Results In Clinical Practicementioning
confidence: 99%
“…Existing models for predicting an individual asthma or COPD patient's health outcomes typically have low accuracy . The systematic review by Loymans et al [52] and our review [43] showed that for forecasting hospital use (emergency department visits and inpatient stays) for asthma in patients with asthma, each previous model, excluding the models of Zein et al [58], has an area under the receiver operating characteristic curve (AUC) within 0.61-0.81, a sensitivity within 25%-49%, and a positive predictive value within 4%-22% [46][47][48][49][50][51][52][53][54][55][56][57]. The models of Zein et al [58] and our recent new models [43][44][45] have similarly higher accuracy but are still not good enough for aligning preventive care with the patients needing it the most.…”
Section: Gap 1: Low Prediction Accuracymentioning
confidence: 99%
See 1 more Smart Citation